PREFERENSI KONSUMEN TERHADAP PEMBELIAN SAYURAN SEGAR BAYAM (AMARANTHUS Sp) DI PASAR TRADISIONAL FLAMBOYAN KOTA PONTIANAK - Sri Widarti; Asti Asti; Donna Youlla; Natalia Nela (Pusat Publikasi Jurnal Universitas Islam Kalimantan, 2026)
This study aims to analyze consumer preferences in purchasing spinach at the Flamboyan Traditional Market and to identify the attributes considered in spinach purchasing decisions. The sampling method used was accidental sampling, involving 100 respondents determined using the Lemeshow formula. Data were collected through structured interviews using questionnaires. The variables examined in this study include price, color, physical appearance, and packaging. Conjoint analysis was employed to assess consumer preferences in spinach purchasing, while descriptive analysis was used to identify the attributes considered in vegetable purchasing decisions. Consumer attitudes toward green spinach were further analyzed using cross-tabulation. The results indicate a high level of accuracy in measuring consumer preferences for spinach purchases. Among the attributes studied, physical appearance was found to be the most important factor influencing consumer purchasing decisions.